An Analysis of Gender Gap in Access to Extension Services - Manoshi Baruah Deka, Pompi Saikia2and Rekha Moni Saikia, (Indian Journal of Extension Education, 2018)
Women produce between 60 -80 percent of food in most developing countries and are responsible for half of the world'sfood production with fewer resources, less access to technology and the added responsibility of child and family but theyreceive little or no support from mainstream agricultural extension services. This paper reports information on genderdifferentials in access to extension services in the state of Assam . Using a cross-sectional study design, data was collectedfrom a random sample of 1100 farm families. In majority (53.20 %) of the households, men owned land compared to 31.5per cent and 15.3 per cent that was either jointly owned or by women. Both rural women and men included as respondentsin the present study possessed knowledge of different extension personnel, Access to extension information wasdominated by 47.5 per cent of the men while only 32.5 per cent of the women had access. Reasons given for nonparticipation was that the shortage of time for both rural women and men (58.23 %) ,sometimes it was because organisingwithout prior notice (48.11 %) and also venue and time not suitable to participate. However, there is a gender bias on thepart of the institutions providing extension services. Findings show that despite the women's important role in agriculturalproduction, disparities exist in the receiving extension services and training programmes in the province. Factors shapingthe gender gap were found to be due to notions about who is a farmer and narrow definition of women's roles inagriculture, targeting rural women as extension clients and targeting male extension agents. It is strongly recommended totrain men extension agents in culturally acceptable methods of delivering extension services to women along withalternate extension methodologies such as ICTs.